Joint Types of Keel and Frame of Wooden Boats Built with Modular System - Akhmad Basuki Widodo; Mochammad Arief Sofijanto (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2023)
The ocean's potential has not been fully exploited to date, with only 40 per cent of the ocean's potential being used. This is due to inadequate facilities and infrastructure. The lack of infrastructure and facilities is due to many factors. One of them is the lack of fishing boats compared to the existing potential. This is because it takes a long time to build a fishing boat. In addition, the existing fishing boats are not powerful enough to travel up to 200 nautical miles. The way out of these problems is to build wooden boats using a modular system. This modular system is expected to produce fishing boats quickly but with a qualified construction. The problem in the production process with this modular system lies in the connection between the keel and the frame. The joint is a critical part in the construction of wooden boats where the joint must be able to withstand dynamic loads. The advantage of wooden boats built with this modular system is that the production process is relatively shorter, which can reduce production costs. The results of tests carried out have shown that the tongue-and-groove type of joint on the keel has a better bending test than the oblique hook type of joint used by traditional boatbuilders. The frame connection type with internal reinforcement has the highest strength among the connection types commonly used by boatwrights and the type of frame connection reinforced on the left and right sides.